Detection of Membrane Protein Two-Dimensional Crystals in Living Cells - Gualtieri, E.J. (The Biophysical Society, 2011)
It is notoriously difficult to grow membrane protein crystals and solve membrane protein structures. Improved detection and screening of membrane protein crystals are needed. We have shown here that second-order nonlinear optical imaging of chiral crystals based on second harmonic generation can provide sensitive and selective detection of two-dimensional protein crystalline arrays with sufficiently low background to enable crystal detection within the membranes of live cells. The method was validated using bacteriorhodopsin crystals generated in live Halobacterium halobium bacteria and confirmed by electron microscopy from the isolated crystals. Additional studies of alphavirus glycoproteins indicated the presence of localized crystalline domains associated with virus budding from mammalian cells. These results suggest that in vivo crystallization may provide a means for expediting membrane protein structure determination for proteins exhibiting propensities for two-dimensional crystal formation.